2020
DOI: 10.1111/adj.12758
|View full text |Cite
|
Sign up to set email alerts
|

National Study of Adult Oral Health 2017–18: Study design and methods

Abstract: The National Study of Adult Oral Health (NSAOH) is Australia’s third national oral examination survey of a representative sample of Australian adults. The study was undertaken primarily to describe levels of oral health in the population and to describe trends since the first survey, conducted in 1987–88. The aim of the study was to complete 7,200 examinations, necessitating approximately 15,200 completed interviews. Survey participants were selected using a multi‐stage probability sampling design that began w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 1 publication
0
30
0
Order By: Relevance
“…This proportion is higher than the 26.5% reported by Jamieson and Thomson (2020) in their analysis of xerostomia in the 75 + year group responding to Australia's National Survey of Adult Oral Health 2017-2018; we did not objectively measure salivary gland function but relied on self-reporting of symptoms and visual signs, such as viscosity. 11,12 This suggests that those in residential care are more likely to have xerostomia potentially due to co-morbidities and their care support needs. Almost half (48.3%) of the participants had dental caries present; one in 10 participants had four or more carious lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This proportion is higher than the 26.5% reported by Jamieson and Thomson (2020) in their analysis of xerostomia in the 75 + year group responding to Australia's National Survey of Adult Oral Health 2017-2018; we did not objectively measure salivary gland function but relied on self-reporting of symptoms and visual signs, such as viscosity. 11,12 This suggests that those in residential care are more likely to have xerostomia potentially due to co-morbidities and their care support needs. Almost half (48.3%) of the participants had dental caries present; one in 10 participants had four or more carious lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Study methodology, including computation of sample size, has been described in previous studies [ 12 , 13 ]. Briefly, a cross-sectional study of a random sample of Australians aged 15 years and over was carried out across all Australian states and territories, employing a three-stage stratified probability sampling design.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure representativeness of the target population, all data were weighted to population benchmarks [ 13 ]. Data files were managed and summary variables were computed using SAS software version 9.4 (SAS 9.4; SAS Institute Inc., Cary, NC, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Data were obtained from the National Survey of Adult Oral Health (NSAOH 2004–06) and the National Study of Adult Oral Health (NSAOH 2017–18). Both were population‐based cross‐sectional surveys of Australian adults aged 15 years or more 12,13 . In the two surveys, representative samples of adults were drawn through a three‐stage, stratified sample design within metropolitan and regional areas in each state/territory.…”
Section: Methodsmentioning
confidence: 99%
“…This is especially crucial for groups recognised as being of greater vulnerability to poor oral health outcomes. The aim of this study was to quantify both self‐reported and clinical oral health outcomes of Indigenous and non‐Indigenous Australians taking part in the 2004‐06 and 2017‐18 national oral health surveys in Australia 12,13 . The hypotheses were as follows: (i) indicators of self‐reported and clinical oral health outcomes in the 2017‐18 survey would be better than those in the 2004‐06 survey for both Indigenous and non‐Indigenous Australians and; (ii) differences between Indigenous and non‐Indigenous Australians oral health outcomes would narrow between surveys.…”
Section: Introductionmentioning
confidence: 99%